Improving students' vocabulary mastery through picture cards - Makaruku, Hendrik (LingTera, 2021)
This study aims to improve the vocabulary mastery of VII grade students of SMP Negeri 4 Taniwel, West Seram, Mollucas, through the use of picture cards. This research was classroom action research. The research subjects were grade VII students of SMP Negeri 4 Taniwel, West Seram, Mollucas, consisting of 24 students. The techniques for collecting the data were observation and interview, whereas the instruments for collecting data were observation checklists, field notes, and tests. The data analysis using qualitative analysis and quantitative analysis. The qualitative analysis was related to the result analysis of the observation, interview, field notes, and observation checklist, while the quantitative analysis was related to the analysis process of simple statistics from the students' test results. The result of the research indicates that the use of picture cards can improve the students' vocabulary mastery, as shown by the students' test results that improved in each cycle. The students' vocabulary mastery was said "improved" if their percentage of completeness overall achieved the indicator of success â‰¥85%. In the first cycle, the percentage of the students' completeness overall improved to 75% with an average score of 74.1 but did not achieve the indicator of success. Therefore, the cycle was repeated in the second cycle with some improvements. In the second cycle, the percentage of the students' completeness overall achieved the indicator of success 91.6% or â‰¥85%. It meant that the student's vocabulary mastery has improved in the second cycle, and the cycle was ended.